Readibility, Meaning, and Function of Foreign Language on Billboards in Surakarta: A Critical Discourse Analysis - Wahyu Joko Saputra; Slamet Subiyantoro; Budhi Setiawan (Humanus, 2020)
This research aims to describe the use of foreign languages on billboards in Surakarta. This research was a single case study obtained from the objective data of billboards along Slamet Riyadi Street Surakarta. The data sources were from the commercial billboards considering several criteria that have been determined in which the billboards should not be owned by either district government or individual,  for campaign purposes, made in 2018, and so on. Those billboards are billboard from Gofood, McDonald's, and Samsung Galaxy Note9. Subsequently, effective data were obtained through observation and interview from informants in readability process. Manifestation of billboard as a form of discourse generates meaning based on critical discourse analysis approach. In addition to the function of billboard as marketing aspect of the company, it also functions to deliver important information, knowledge, and educative information for the readers. This research results show that the readability, meaning, and function of foreign languages assumption on advertisement of billboard are different from the marketing concept. Nonetheless, an emergence of foreign languages provides space for the readers to learn the vocabulary in facing globalization era. Moreover, it also reminds us not to forget the existing culture in Surakarta.